Dr. Jekyll y Mr. Hyde - Gray, Elizabeth (Showtime readers)
26 March 1886, I cannot control him any longer. He comes when he wants and there is nothing I can do about it. Soon, everyone will know. What can I do? He´s coming. I know he is. I can feel it. This time he will stay for ever